Papanicolaou induced fluorescence, Ziehl‐Neelsen and Auramine O stains on lymph node fine needle aspiration biopsy specimens from children: A comparative study. Issue 7 (3rd May 2018) - Selepe, Malesiba Mampotoko; van Wyk, Abraham Christoffel; Hoek, Kim Gilberte Pauline; Prince, Yvonne; van Helden, Paul David; Warren, Robin Mark; Wright, Colleen Anne
Abstract : Background: The rapid diagnosis of extrapulmonary tuberculosis in children remains challenging. The presence of enlarged lymph nodes provides an opportunity to obtain diagnostic material through fine needle aspiration biopsy (FNAB). Mycobacterial culture, traditionally the reference standard, has a slow turnaround time and PCR‐based methods are not widely available in developing countries. Direct visualization of mycobacteria on microscopy can be a rapid method to confirm the diagnosis. This study compared three staining methods to visualize mycobacteria. Methods: Hundred FNAB specimens from persistently enlarged lymph nodes in children, clinically suspicious for tuberculosis, were evaluated for the presence of mycobacteria by three staining methods: Papanicolaou induced fluorescence (PIF) and Auramine O staining using fluorescence microscopy and Ziehl‐Neelsen (ZN) staining using conventional light microscopy. These methods were evaluated against mycobacterial culture. Results: PIF positivity was 30%, with 38% and 48% for Auramine O and ZN respectively. The combined ZN/PIF positivity was 56%. The highest diagnostic accuracy (73%) was demonstrated by ZN alone and in combination with PIF, with PIF alone showing the lowest (49%) accuracy. Although the combined test showed the highest sensitivity, it had the lowest specificity, while ZN was significantly more sensitive than both other staining modalities. No statistical difference in specificity was seen among the tests. Conclusion: This study suggests that Auramine O staining on previously ZN stained slides does not significantly improve diagnostic accuracy. While currently widely available methods of direct visualization of mycobacteria suffer from low sensitivity, the ZN stain remains a useful diagnostic test, particularly in resource‐constrained countries.